DEVELOPING A BILINGUAL PRODUCT CATALOGUE FOR SME BATIK SENDANG LESTARI BLITAR - Tristiawan, Mahardika Isaura (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
Product promotion is an important factor in the development of an MSME. This product catalogue was developed in two languages. The Research was conducted at SME Batik Sendang Lestari, located in Blitar City. The aim of this study is to develop Bilingual Product Catalogue for SME Batik Sendang Lestari Blitar. The research adopted the Design and Development Research (DDR) method. The stages used in this research are Analysis, Design, Development, Implementation, Evaluation. The result was Bilingual Product Catalogue for SME Batik Sendang Lestari Blitar which has 16 pages and consist of 15 products. The catalogue was successful be implemented along with positive response from 35 respondents. It implies that this product catalogue can facilitate selling activities and introduce SME Batik Sendang Lestari to be recognized by the wider community including foreign tourists.